Composite science and technology : selected, peer reviewed papers from the Eight International Conference on Composite Science and Technology (ICCST8), 22-24 March 2011, Kuala Lumpur, Malaysia - Sapuan, S. M. (Trans Tech Publications, 2011)
Volume is indexed by Thomson Reuters CPCI-S (WoS).This collection of more than 204 peer-reviewed papers on Composite Science and Technology covers: mechanics of composites, infrastructural composites, non-destructive evaluation and characterization of composites, fracture and fatigue of composites, numerical and mathematical modelling, ceramic matrices, composites, metal-matrix composites, composite manufacturing, polymer composites, smart materials and structures, nano-composites, bio-composites and structural health monitoring. This makes it a handy guide to the state-of-the-art of this field. This two-volume collection of more than two hundred articles on composite materials, comprising selected papers presented at the Eighth International Conference on Composite Science and Technology, held in March 2011 in Kuala Lumpur, Malaysia, showcases current scholarship in engineering for a wide range of industrial and research processes. Articles cover a wide range of composite engineering topics, ranging from electronics assembly technologies and aerospace materials testing to transportation technologies and metallic alloy chemistry. Individual essays include relevant illustrations, tables and data sets as well as abstracts, notes and bibliographies. Both key word and author indexes are provided. Contributors are academics from major universities around the world as well as working engineers representing international firms.
Keywords: Composite materials -- Congresses.; elektronické knihy; electronic books